Olfactory dysfunction: a diagnostic symptom of COVID-19 - Shaila Kabir; A B M Tofazzal Hossain; M. Tanveer Hossain Parash; Liew, Constance Sat Lin; Chandrika Murugaiah; A. H. M. Delwar; M. Alamgir Chowdhury (Universiti Malaysia Sabah, 2021)
Besides the common respiratory symptoms or viral pneumonia, COVID-19 is also presented with different neurological symptoms. Olfactory dysfunction (OD) or impairment of the sense of smell is one of the common neurological symptoms being reported in infection caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The severity varies from anosmia to microsmia or hyposmia. OD could have a potential early screening and diagnostic value besides other neurological and common respiratory symptoms. In our descriptive concise review, we aimed to elicit the manifestation of olfactory dysfunction as an early predictor of SARS-CoV-2 infection. We are also aiming to establish, OD as a quick and reliable assessment tool of COVID-19 risk, among the healthcare workers and contact tracers, which can justify self-quarantine of the person as well as recommendation for testing on a priority basis. We have also focused on, any effect to produce this symptom by the drug used for treatment in COVID-19, and if the old age of the patient showing any extra influence to develop OD in COVID-19.